Artifact bb38f73c9a9c8bed6343dd8e83248f6a7194b0f9ecf691ded30063c69d915a96:
- File
r36/doc/ZTRANS.TEX
— part of check-in
[152fb3bdbb]
at
2011-10-17 17:58:33
on branch master
— svn:eol-style, svn:executable and line endings for files
in historical/r36 treegit-svn-id: https://svn.code.sf.net/p/reduce-algebra/code/trunk/historical@1480 2bfe0521-f11c-4a00-b80e-6202646ff360 (user: schoepf@users.sourceforge.net, size: 11925) [annotate] [blame] [check-ins using] [more...]
\documentstyle[11pt,reduce]{article} \title{{\bf $Z$-Transform Package for {\tt REDUCE}}} \author{Wolfram Koepf \\ Lisa Temme \\ email: {\tt Koepf@zib-berlin.de}} \date{April 1995 : ZIB Berlin} \begin{document} \maketitle \section{$Z$-Transform} The $Z$-Transform of a sequence $\{f_n\}$ is the discrete analogue of the Laplace Transform, and \[{\cal Z}\{f_n\} = F(z) = \sum^\infty_{n=0} f_nz^{-n}\;.\] \\ This series converges in the region outside the circle $|z|=|z_0|= \limsup\limits_{n \rightarrow \infty} \sqrt[n]{|f_n|}\;.$ \begin{tabbing} {\bf SYNTAX:}\ \ {\tt ztrans($f_n$, n, z)}\ \ \ \ \ \ \ \ \=where $f_n$ is an expression, and $n$,$z$ \\ \> are identifiers.\\ \end{tabbing} \section{Inverse $Z$-Transform} The calculation of the Laurent coefficients of a regular function results in the following inverse formula for the $Z$-Transform: \\ If $F(z)$ is a regular function in the region $|z|> \rho$ then $\exists$ a sequence \{$f_n$\} with ${\cal Z} \{f_n\}=F(z)$ given by \[f_n = \frac{1}{2 \pi i}\oint F(z) z^{n-1} dz\] \begin{tabbing} {\bf SYNTAX:}\ \ {\tt invztrans($F(z)$, z, n)}\ \ \ \ \ \ \ \ \=where $F(z)$ is an expression, \\ \> and $z$,$n$ are identifiers. \end{tabbing} \section{Input for the $Z$-Transform} \begin{tabbing} This pack\=age can compute the \= $Z$-Transforms of the \=following list of $f_n$, and \\ certain combinations thereof.\\ \\ \>$1$ \>$e^{\alpha n}$ \>$\frac{1}{(n+k)}$ \\ \\ \>$\frac{1}{n!}$ \>$\frac{1}{(2n)!}$ \>$\frac{1}{(2n+1)!}$ \\ \\ \>$\frac{\sin(\beta n)}{n!}$ \>$\sin(\alpha n+\phi)$ \>$e^{\alpha n} \sin(\beta n)$ \\ \\ \>$\frac{\cos(\beta n)}{n!}$ \>$\cos(\alpha n+\phi)$ \>$e^{\alpha n} \cos(\beta n)$ \\ \\ \>$\frac{\sin(\beta (n+1))}{n+1}$ \>$\sinh(\alpha n+\phi)$ \>$\frac{\cos(\beta (n+1))}{n+1}$ \\ \\ \>$\cosh(\alpha n+\phi)$ \>${n+k \choose m}$\\ \end{tabbing} \begin{tabbing} \underline {{\bf Other Combinations}}\= \\ \\ \underline {Linearity} \>${\cal Z} \{a f_n+b g_n \} = a{\cal Z} \{f_n\}+b{\cal Z}\{g_n\}$ \\ \\ \underline {Multiplication by $n$} \>${\cal Z} \{n^k \cdot f_n\} = -z \frac{d}{dz} \left({\cal Z}\{n^{k-1} \cdot f_n,n,z\} \right)$ \\ \\ \underline {Multiplication by $\lambda^n$} \>${\cal Z} \{\lambda^n \cdot f_n\}=F \left(\frac{z}{\lambda}\right)$ \\ \\ \underline {Shift Equation} \>${\cal Z} \{f_{n+k}\} = z^k \left(F(z) - \sum\limits^{k-1}_{j=0} f_j z^{-j}\right)$ \\ \\ \underline {Symbolic Sums} \> ${\cal Z} \left\{ \sum\limits_{k=0}^{n} f_k \right\} = \frac{z}{z-1} \cdot {\cal Z} \{f_n\}$ \\ \\ \>${\cal Z} \left\{ \sum\limits_{k=p}^{n+q} f_k \right\}$ \ \ \ combination of the above \\ \\ where $k$,$\lambda \in$ {\bf N}$- \{0\}$; and $a$,$b$ are variables or fractions; and $p$,$q \in$ {\bf Z} or \\ are functions of $n$; and $\alpha$, $\beta$ \& $\phi$ are angles in radians. \end{tabbing} \section{Input for the Inverse $Z$-Transform} \begin{tabbing} This \= package can compute the Inverse \= Z-Transforms of any rational function, \\ whose denominator can be factored over ${\bf Q}$, in addition to the following list \\ of $F(z)$.\\ \\ \> $\sin \left(\frac{\sin (\beta)}{z} \ \right) e^{\left(\frac{\cos (\beta)}{z} \ \right)}$ \> $\cos \left(\frac{\sin (\beta)}{z} \ \right) e^{\left(\frac{\cos (\beta)}{z} \ \right)}$ \\ \\ \> $\sqrt{\frac{z}{A}} \sin \left( \sqrt{\frac{z}{A}} \ \right)$ \> $\cos \left( \sqrt{\frac{z}{A}} \ \right)$ \\ \\ \> $\sqrt{\frac{z}{A}} \sinh \left( \sqrt{\frac{z}{A}} \ \right)$ \> $\cosh \left( \sqrt{\frac{z}{A}} \ \right)$ \\ \\ \> $z \ \log \left(\frac{z}{\sqrt{z^2-A z+B}} \ \right)$ \> $z \ \log \left(\frac{\sqrt{z^2+A z+B}}{z} \ \right)$ \\ \\ \> $\arctan \left(\frac{\sin (\beta)}{z+\cos (\beta)} \ \right)$ \\ \end{tabbing} where $k$,$\lambda \in$ {\bf N}$ - \{0\}$ and $A$,$B$ are fractions or variables ($B>0$) and $\alpha$,$\beta$, \& $\phi$ are angles in radians. \section{Application of the $Z$-Transform} \underline {{\bf Solution of difference equations}}\\ In the same way that a Laplace Transform can be used to solve differential equations, so $Z$-Transforms can be used to solve difference equations.\\ \\ Given a linear difference equation of $k$-th order \begin{equation} f_{n+k} + a_1 f_{n+k-1}+ \ldots + a_k f_n = g_n \label{eq:1} \end{equation} with initial conditions $f_0 = h_0$, $f_1 = h_1$, $\ldots$, $f_{k-1} = h_{k-1}$ (where $h_j$ are given), it is possible to solve it in the following way. If the coefficients $a_1, \ldots , a_k$ are constants, then the $Z$-Transform of (\ref{eq:1}) can be calculated using the shift equation, and results in a solvable linear equation for ${\cal Z} \{f_n\}$. Application of the Inverse $Z$-Transform then results in the solution of \ (\ref{eq:1}).\\ If the coefficients $a_1, \ldots , a_k$ are polynomials in $n$ then the $Z$-Transform of (\ref{eq:1}) constitutes a differential equation for ${\cal Z} \{f_n\}$. If this differential equation can be solved then the Inverse $Z$-Transform once again yields the solution of (\ref{eq:1}). Some examples of these methods of solution can be found in $\S$\ref{sec:Examples}. \section{EXAMPLES} \label{sec:Examples} \underline {{\bf Here are some examples for the $Z$-Transform}}\\ \begin{verbatim} 1: ztrans((-1)^n*n^2,n,z); z*( - z + 1) --------------------- 3 2 z + 3*z + 3*z + 1 2: ztrans(cos(n*omega*t),n,z); z*(cos(omega*t) - z) --------------------------- 2 2*cos(omega*t)*z - z - 1 3: ztrans(cos(b*(n+2))/(n+2),n,z); z z*( - cos(b) + log(------------------------------)*z) 2 sqrt( - 2*cos(b)*z + z + 1) 4: ztrans(n*cos(b*n)/factorial(n),n,z); cos(b)/z sin(b) sin(b) e *(cos(--------)*cos(b) - sin(--------)*sin(b)) z z --------------------------------------------------------- z 5: ztrans(sum(1/factorial(k),k,0,n),n,z); 1/z e *z -------- z - 1 6: operator f$ 7: ztrans((1+n)^2*f(n),n,z); 2 df(ztrans(f(n),n,z),z,2)*z - df(ztrans(f(n),n,z),z)*z + ztrans(f(n),n,z) \end{verbatim} \underline {{\bf Here are some examples for the Inverse $Z$-Transform}} \begin{verbatim} 8: invztrans((z^2-2*z)/(z^2-4*z+1),z,n); n n n (sqrt(3) - 2) *( - 1) + (sqrt(3) + 2) ----------------------------------------- 2 9: invztrans(z/((z-a)*(z-b)),z,n); n n a - b --------- a - b 10: invztrans(z/((z-a)*(z-b)*(z-c)),z,n); n n n n n n a *b - a *c - b *a + b *c + c *a - c *b ----------------------------------------- 2 2 2 2 2 2 a *b - a *c - a*b + a*c + b *c - b*c 11: invztrans(z*log(z/(z-a)),z,n); n a *a ------- n + 1 12: invztrans(e^(1/(a*z)),z,n); 1 ----------------- n a *factorial(n) 13: invztrans(z*(z-cosh(a))/(z^2-2*z*cosh(a)+1),z,n); cosh(a*n) \end{verbatim} \underline {{\bf Examples: Solutions of Difference Equations}}\\ \\ \begin{tabbing} {\bf I} \ \ \ \ \ \ \= (See \cite{BS}, p.\ 651, Example 1).\\ \> Consider the \= homogeneous linear difference equation\\ \\ \>\> $f_{n+5} - 2 f_{n+3} + 2 f_{n+2} - 3 f_{n+1} + 2 f_{n}=0$\\ \\ \> with \ initial conditions \ $f_0=0$, $f_1=0$, $f_2=9$, $f_3=-2$, $f_4=23$. \ The\\ \> $Z$-Transform of the left hand side can be written as $F(z)=P(z)/Q(z)$ \\ \> where \ $P(z)=9z^3-2z^2+5z$ \ and \ $Q(z)=z^5-2z^3+2z^2-3z+2$ \ $=$\\ \> $(z-1)^2(z+2)(z^2+1)$, \ which can be inverted to give\\ \\ \>\> $f_n = 2n + (-2)^n - \cos \frac{\pi}{2}n\;.$ \\ \\ \> The following REDUCE session shows how the present package can \\ \> be used to solve the above problem. \end{tabbing} \begin{verbatim} 14: operator f$ f(0):=0$ f(1):=0$ f(2):=9$ f(3):=-2$ f(4):=23$ 20: equation:=ztrans(f(n+5)-2*f(n+3)+2*f(n+2)-3*f(n+1)+2*f(n),n,z); 5 3 equation := ztrans(f(n),n,z)*z - 2*ztrans(f(n),n,z)*z 2 + 2*ztrans(f(n),n,z)*z - 3*ztrans(f(n),n,z)*z 3 2 + 2*ztrans(f(n),n,z) - 9*z + 2*z - 5*z 21: ztransresult:=solve(equation,ztrans(f(n),n,z)); 2 z*(9*z - 2*z + 5) ztransresult := {ztrans(f(n),n,z)=----------------------------} 5 3 2 z - 2*z + 2*z - 3*z + 2 22: result:=invztrans(part(first(ztransresult),2),z,n); n n n n 2*( - 2) - i *( - 1) - i + 4*n result := ----------------------------------- 2 \end{verbatim} \begin{tabbing} \\ \\ {\bf II} \ \ \ \ \ \ \= (See \cite{BS}, p.\ 651, Example 2).\\ \> Consider the \= inhom\=ogeneous difference equation:\\ \\ \>\> $f_{n+2} - 4 f_{n+1} + 3 f_{n} = 1$\\ \\ \> with initial conditions $f_0=0$, $f_1=1$. Giving \\ \\ \>\> $F(z)$\>$ = {\cal Z}\{1\} \left( \frac{1}{z^2-4z+3} + \frac{z}{z^2-4z+3} \right)$\\ \\ \>\>\> $ = \frac{z}{z-1} \left( \frac{1}{z^2-4z+3} + \frac{z}{z^2-4z+3} \right)$. \\ \\ \> The Inverse $Z$-Transform results in the solution\\ \\ \>\> $f_n = \frac{1}{2} \left( \frac{3^{n+1}-1}{2}-(n+1) \right)$.\\ \\ \> The following REDUCE session shows how the present package can\\ \> be used to solve the above problem. \end{tabbing} \begin{verbatim} 23: clear(f)$ operator f$ f(0):=0$ f(1):=1$ 27: equation:=ztrans(f(n+2)-4*f(n+1)+3*f(n)-1,n,z); 3 2 equation := (ztrans(f(n),n,z)*z - 5*ztrans(f(n),n,z)*z 2 + 7*ztrans(f(n),n,z)*z - 3*ztrans(f(n),n,z) - z )/(z - 1) 28: ztransresult:=solve(equation,ztrans(f(n),n,z)); 2 z result := {ztrans(f(n),n,z)=---------------------} 3 2 z - 5*z + 7*z - 3 29: result:=invztrans(part(first(ztransresult),2),z,n); n 3*3 - 2*n - 3 result := ---------------- 4 \end{verbatim} \begin{tabbing} \\ \\ {\bf III} \ \ \ \ \ \ \= Consider the \=following difference equation, which has a differential\\ \> equation for ${\cal Z}\{f_n\}$.\\ \\ \>\> $(n+1) \cdot f_{n+1}-f_n=0$\\ \\ \> with initial conditions $f_0=1$, $f_1=1$. It can be solved in REDUCE\\ \> using the present package in the following way.\\ \end{tabbing} \begin{verbatim} 30: clear(f)$ operator f$ f(0):=1$ f(1):=1$ 34: equation:=ztrans((n+1)*f(n+1)-f(n),n,z); 2 equation := - (df(ztrans(f(n),n,z),z)*z + ztrans(f(n),n,z)) 35: operator tmp; 36: equation:=sub(ztrans(f(n),n,z)=tmp(z),equation); 2 equation := - (df(tmp(z),z)*z + tmp(z)) 37: load(odesolve); 38: ztransresult:=odesolve(equation,tmp(z),z); 1/z ztransresult := {tmp(z)=e *arbconst(1)} 39: preresult:=invztrans(part(first(ztransresult),2),z,n); arbconst(1) preresult := -------------- factorial(n) 40: solve({sub(n=0,preresult)=f(0),sub(n=1,preresult)=f(1)}, arbconst(1)); {arbconst(1)=1} 41: result:=preresult where ws; 1 result := -------------- factorial(n) \end{verbatim} \begin{thebibliography}{9} \bibitem{BS} Bronstein, I.N. and Semedjajew, K.A., {\it Taschenbuch der Mathematik}, Verlag Harri Deutsch, Thun und Frankfurt(Main), 1981.\\ISBN 3 87144 492 8. \end{thebibliography} \end{document}